Syro-Melkite manuscript of the 15th century (vat. Sir. 351): an unfinished project of the monthly Menaion for the whole year in one volume - Aleksandr Lukashevich (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article describes contents, paleographic, linguistic, and liturgical features of one of the Syriac manuscripts of the Vatican Library, Vat. sir. 351, dating back to the 15th century. A large part of the manuscript is written by one scribe with a very fine and professional handwriting, but there are also insertions of other scribes, two of them we know by their names indicated in the margins (Yusuf, Salam). The manuscript is written mostly in classical Syriac, but some rubrics and texts are written in Arabic. The Menaion contains texts of the Holy Scripture: readings from the Apostol and the Gospel in the beginning of the manuscript, then in the Menaion part — prokimena, alleluiaria, communion hymns, New Testament readings for matins and liturgy, psalms of the great hours and selected psalms (eklogai) for singing after the polyeleos on great feasts. We may suggest that the scribe planned to include the entire Menaion for the whole year, from September to August, in one volume. However, this experiment remained incomplete: services for every day can be found only in the beginning and in the end of the manuscript (months of September, October, part of November, August), while other months contain a selection of the most festive days. Thus, the manuscript cannot be fully characterized by terms like a “Monthly Menaion” or a “Festal Menaion”. Days without services contain only indications of the date, names of the saints, often with addition of stichera, troparion and kontakion, always with indications of readings for the liturgy; the scribe usually left an empty space after the date, due to lack of time or inability to find the necessary texts. The changes from daily services to festive selection and vice versa are situated not far from large portions written by other scribes.